Real rectifiable currents, holomorphic chains and algebraic cycles - Teh Jyh-Haur (De Gruyter, 2021)
We study some fundamental properties of real rectifiable currents and give a generalization of King’s theorem to characterize currents defined by positive real holomorphic chains. Our main tool is Siu’s semi-continuity theorem and our proof largely simplifies King’s proof. A consequence of this result is a sufficient condition for the Hodge conjecture.